(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Advantageous cultivation procedures for the Chinese hamster ovary (CHO) cells are necessary for the productive commercial production of biopharmaceuticals. A main challenge that needs to be addressed during the process development is the differences in each cell line requirements concerning the nutrients and feed strategies in order to achieve the desired growth characteristics. Therefore, within the current research, a naïve high cell density serum free suspension adapted CHO cell line was tested with glucose and glutamine rich feeds in fed-batch Erlenmeyer shake flask cultures. Glucose consumption rate was adjusted to develop the optimal feed strategies. Obtained results indicated that high glucose and l-glutamine feeding did not improve maximum viable cell density compared to the control samples. During the exponential phase, cell proliferation and viability of all feeds showed no statistically significant difference. Instead, the fed-batch processes tested led to statistically significant differences in viable cell density and cell viability during the decline phase, compared to control (batch) culture. The difference between glucose and glutamine feeding was indistinguishable, most probably due to the concentration imbalance with the rest of the nutrients in feed. The overall study presented a method to slow down the decrease in CHO cell proliferation and viability during the decline phase, instead of increasing the maximum cell density at the plateau phase.